MEDIA EDUCATION IN UKRAINE: LEGISLATIVE PROVISION ANALYSIS - Golovchenko, Glib (Educological discourse, 2020)
Today, in a digital society, media and information literacy, which is the result of media education, is considered vital. The importance of media education is acknowledged by Ukrainian authorities, researchers, practicing teachers, public organizations. Hence, Ukraine has acquired some experience in providing media education. The goal of the article is to analyze media education in Ukraine from the standpoint of regulatory and legal support and the experience of its practical implementation. A complex of scientific research methods was used to achieve the established goal: overview of literature and legislative documents; analysis, synthesis of the obtained results, prognostic method. It was found out that a number of legal documents regulate the activities of the media sphere in Ukraine. However, the vast majority of them refer to the activities of the media or the regulation of the information sphere. Instead, the development of media information literacy is regulated not by a separate law, but in the context of a number of more global laws of Ukraine on education. Priority areas for further development of media education are defined in the Concept of media education for the period up to 2025. The analysis of the Concept regarding the forms of media education and the tasks facing them were analyzed. 7 forms of media education were characterized in the article: pre-school, school, out-of-school, higher school, for parents, for adults, non-formal media education. Inadequacy of using the term “media education through media” as non-formal media education was proved. The expediency of differentiating terms “non-formal” and “informal” media education was substantiated. Hence, one more form of media education was distinguished – "self-education through media". It is defined as a self-organized acquisition of digital, informational and media competencies during daily activities related to professional, social or other activities, family or leisure. The perspectives of further research were outlined, particularly as an empirical investigation.